Cytoplasmic mRNA: move it, use it or lose it!. (24th November 2010) - Coldwell, Mark J.; Gray, Nicola K.; Brook, Matthew
Abstract : Once an mRNA is synthesized and processed, the immediate translation and later destruction of the transcript is not as inevitable as the central molecular biology dogma suggests. Interest in the field of post-transcriptional control continues to grow rapidly, as regulation of these multiple steps in gene expression is implicated in diverse aspects of biology such as metabolism, neurology, reproduction and viral lifecycle regulation. Researchers who utilize various combinations of human studies, animal models, cellular, genetic, biochemical and molecular techniques were brought together at the University of Edinburgh to discuss their latest findings. In this article, we introduce the content of the related reviews presented in this issue of Biochemical Society Transactions which together illustrate a major theme of the meeting content: namely the need to understand how dynamic changes in mRNP (messenger ribonucleoprotein) complexes modulate the multifunctionality of regulatory proteins which link different post-transcriptional regulatory events.